The influence of corporate brand perceptions on consumer satisfaction and loyalty via controlled and uncontrolled communications: a multiple mediation analysis. Issue 1 (16th January 2019) - Anisimova, Tatiana; Weiss, Jan; Mavondo, Felix
Abstract : Purpose: Drawing on the stimulus–organism–response (S-O-R) model, the purpose of this study is to investigate mediating effects of controlled and uncontrolled communications of corporate brand perceptions on consumer satisfaction and loyalty. Design/methodology/approach: Structural equation modeling (SEM) was used to test the hypotheses on a sample of 271 Australian automobile consumers. Findings: The authors find that while consumer satisfaction is indirectly influenced by corporate-level attributes via controlled and uncontrolled communication, the authors did not find an indirect effect between consumer benefits on consumer satisfaction via controlled and uncontrolled communication. By contrast, the authors find highly significant indirect effects – via controlled and uncontrolled communication as well as consumer satisfaction – for the relationship between, on the one hand, corporate-level attributes and consumer benefits and consumer brand loyalty on the other. Uncontrolled communication was significantly associated with consumer loyalty, a relevant finding that indicates an importance of tracking media coverage and maintaining favorable relationships with the media. Research limitations/implications: The cross-sectional method limits data collection to one point in time. Practical implications: This study adds to a better understanding of how to leverage corporate brand through communications in ways that it positively resonates with consumers. A fine-grained analysis of corporate brand attributes and consumer-perceived benefits can aid managers in developing specific and more effective marketing strategies. Originality/value: The overall thrust of this empirical study, which is to investigate how corporate brand perceptions influence short term (satisfaction) and long term (loyalty) via controlled and uncontrolled communications is original. This study comprehensively conceptualizes and operationalizes the corporate brand as a multidimensional construct consisting of corporate-level attributes and brand-level attributes such as perceived consumer benefits. To examine the hypothesized relationships between and among our constructs, the authors go beyond the commonly studied single mediator model and test a multiple mediator model instead.